Mutational Analyses of the Enzymes Involved in the Metabolism of Hydrogen by the Hyperthermophilic Archaeon Pyrococcus furiosus - Schut, Gerrit J.; Nixon, William J.; Lipscomb, Gina L.; Scott, Robert A.; Adams, Michael (Frontiers in Microbiology, 2012)
Pyrococcus furiosus grows optimally near 100°C by fermenting carbohydrates to produce hydrogen (H2) or, if elemental sulfur (S0), is present hydrogen sulfide instead. It contains two cytoplasmic hydrogenases, SHI and SHII, that use NADP(H) as an electron carrier, and a membrane bound hydrogenase (MBH), that utilizes the redox protein ferredoxin. We previously constructed deletion strains lacking SHI and/or SHII and showed that they exhibited no obvious phenotype. This study has now been extended to include biochemical analyses and growth studies using the ΔSHI and ΔSHII deletion strains together with strains lacking a functional MBH (ΔMbhL). Hydrogenase activities in cytoplasmic extracts of ΔSHII and the parent strain were similar but were much lower (<10%) in the ΔSHI strain, and no activity was detected in the ΔSHIΔSHII double deletion strain, indicating that SHI is responsible for most of the cytoplasmic hydrogenase activity. In contrast, the ΔmbhL strain showed no growth in the absence of S0, confirming the hypothesis that, in the absence of S0, MBH is the only enzyme that can dispose of reductant (as H2) generated during sugar oxidation. The deletion strain devoid of all three hydrogenases also grew only in the presence of S0 and did not produce any detectable H2. When grown in the presence of limiting S0, both H2S and H2 were produced by the parent and ΔSHI/ΔSHII strains. A significant amount of H2 was also produced by the ΔmbhL strain, showing that SHI can produce H2 from NADPH in vivo, although this does not enable significant growth of ΔmbhL in the absence of S0. We propose that the physiological function of SHI is to recycle H2 and provide a link between external H2 and the intracellular pool of NADPH needed for biosynthesis. This likely has a distinct energetic advantage in the environment, but it is clearly not required for growth of the organism under the usual laboratory conditions. The function of SHII, however, remains unknown.